2019
DOI: 10.1007/s13311-019-00761-0
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Administration of IL-13 Induces Anti-inflammatory Microglial/Macrophage Responses and Provides Neuroprotection in Ischemic Stroke

Abstract: Neuroinflammation is strongly induced by cerebral ischemia. The early phase after the onset of ischemic stroke is characterized by acute neuronal injury, microglial activation, and subsequent infiltration of blood-derived inflammatory cells, including macrophages. Therefore, modulation of the microglial/macrophage responses has increasingly gained interest as a potential therapeutic approach for the ischemic stroke. In our study, we investigated the effects of peripherally administered interleukin 13 (IL-13) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 54 publications
5
58
0
Order By: Relevance
“…Our preceding studies have shown that local administration of IL13 at the onset of neuroinflammation promotes alternative activation of lesion-associated myeloid cells in mouse models of spinal cord injury (SCI) (Dooley et al, 2016), cuprizone (CPZ)-induced CNS inflammation and demyelination (Guglielmetti et al, 2016;Le Blon et al, 2016), temporal lobe epilepsy (Ali et al, 2017), and middle cerebral artery occlusion (MCAO)-induced stroke (Hamzei Taj et al, 2018). Furthermore, we and/or others have shown that IL13 treatment is associated with improved histopathological and/or functional recovery in SCI, CPZ, and MCAO models (Dooley et al, 2016;Guglielmetti et al, 2016;Kolosowska et al, 2019;Le Blon et al, 2016), suggesting a rationale for the use of IL13 as a future supportive therapeutic agent in CNS trauma (Quarta, Berneman, & Ponsaerts, 2020).…”
Section: Forced Induction Of Microglia and Monocytes Anti-inflammatorymentioning
confidence: 94%
“…Our preceding studies have shown that local administration of IL13 at the onset of neuroinflammation promotes alternative activation of lesion-associated myeloid cells in mouse models of spinal cord injury (SCI) (Dooley et al, 2016), cuprizone (CPZ)-induced CNS inflammation and demyelination (Guglielmetti et al, 2016;Le Blon et al, 2016), temporal lobe epilepsy (Ali et al, 2017), and middle cerebral artery occlusion (MCAO)-induced stroke (Hamzei Taj et al, 2018). Furthermore, we and/or others have shown that IL13 treatment is associated with improved histopathological and/or functional recovery in SCI, CPZ, and MCAO models (Dooley et al, 2016;Guglielmetti et al, 2016;Kolosowska et al, 2019;Le Blon et al, 2016), suggesting a rationale for the use of IL13 as a future supportive therapeutic agent in CNS trauma (Quarta, Berneman, & Ponsaerts, 2020).…”
Section: Forced Induction Of Microglia and Monocytes Anti-inflammatorymentioning
confidence: 94%
“…Treatment strategies are available to antagonize androgen-mediated effects, which can promote protective ILC2 and Th22 cell responses when initiated early during SARS-CoV-2 infection. Recombinant amphiregulin has shown beneficial effects in influenza-infected mice, and IL-13 has been proposed as a therapeutic intervention to reduce inflammation and promote tissue repair in preclinical models of stroke ( Kolosowska et al., 2019 ). However, given the pro-inflammatory role of cytokines in immune-mediated diseases such as Crohn’s disease and rheumatoid arthritis, as well as enhanced levels detected in COVID-19 patients ( Lucas et al., 2020 ; Mateen et al., 2019 ; Shah et al., 2018 ), the timing of initiation of immune-therapies in SARS-CoV-2 infection will be critical to promote viral containment and tissue resilience without contributing to the cytokine release syndrome in the advanced stages of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…The immune response in neonates is biased toward the Th2 type (Adkins et al, 2004;Debock and Flamand, 2014), but after HI insult there is a Th1/Th17-type immune response in the neonatal mouse brain (Albertsson et al, 2014;Yang et al, 2014) and blockage of lymphocyte trafficking to the brain is neuroprotective (Yang et al, 2014). Further, the Th2 cytokines IL-4 and IL-13 have been found to protect the mouse brain from injury (Walsh et al, 2015;Kolosowska et al, 2019).…”
Section: Introductionmentioning
confidence: 99%